Pendampingan Pengelolaan Manajemen Pemasaran pada Mie Ayam Pak Bari di Desa Tireman Kabupaten Rembang - Nuqman Abdul Rahman; Dian Ayu Liana Dewi (Lembaga Pengembangan Kinerja Dosen, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a crucial pillar of economic development in Indonesia, playing a significant role in job creation, increasing community income, and driving regional economic growth. Mie Ayam Pak Bari is one such MSME located in Tireman Village, Rembang Regency, Central Java. This business is characterized by delicious flavors, affordable prices, and a unique location that lacks similar competitors in the surrounding area. Despite its significant potential, Mie Ayam Pak Bari faces several challenges, including limited marketing reach, limited exposure to local communities, and volatile raw material price fluctuations. To address these challenges, mentoring focused on strengthening business management strategies and increasing marketing effectiveness. The mentoring included creating a banner as the business's visual identity, developing an attractive and informative menu catalog, and establishing an Instagram account to expand online promotional reach. This strategy is expected to attract new customers, increase consumer loyalty, and build a positive image for the business in the eyes of the wider community. The mentoring results indicate an increase in the completeness of promotional tools, the formation of a clearer business identity, and an increase in communication channels with consumers through social media. The menu catalog helps customers understand product variety and pricing transparently, while banners serve as physical markers, making it easier for customers to find the business's location. Meanwhile, the Instagram account serves as an interactive platform that allows businesses to reach potential customers outside of Tireman Village. This mentoring activity demonstrates that implementing visual and digital media-based marketing strategies can be an effective solution for MSMEs to survive and thrive in an increasingly competitive market.